A broadband dual‐polarized filtering base‐station antenna for 5G communication applications. Issue 5 (17th February 2022) - Xi, Yi; Wang, Yani; Zhai, Huiqing; Liu, Changyuan
Abstract: In this article, a broadband dual‐polarized filtering base‐station antenna is proposed. The structure of proposed antenna consists of a main radiation element, two parasitic rings, balun feeding line, and metal reflector. The parasitic ring embedded in the antenna radiating arm not only generates a high‐frequency radiation null, but also expands the antenna bandwidth. At the same time, a parasitic ring is loaded on the back of the substrate to generate a low‐frequency radiation null. These two parasitic rings make full use of the spatial position of the antenna and produce a better filtering effect. In order to verify the feasibility of the antenna, the designed antenna was processed and measured. In the end, the designed antenna achieves an impedance bandwidth of 48.3% (VSWR < 1.5, at 4.35 GHz), the measured average gain is 8.5 dBi. Out‐of‐band suppression at low frequencies (2–2.7 GHz) are greater than 27 dB, and out‐of‐band suppression at high frequencies (6.1–6.5 GHz) are greater than 17 dB. In addition, the antenna covers the 5G communication frequency band under Sub‐6G, which is suitable for 5G base‐station antennas.